Die verstaan en funksie van die Ou Testament in die kerk (of: kan die kerk klaarkom sonder die Ou Testament?) Deel I - S. D. Snyman (Acta Theologica)
The question put in this two part article is suggested in the title: can the church do without the Old Testament? In part I of the article an overview and interpretation of the history of research regarding this matter are given. The result of this investigation boils down to two basic answers given: The Old Testament was either totally rejected or narrowed down to a formula like promise-fulfillment; law-gospel; continuity-discontinuity. However well intended, to narrow down the Old Testament to a single formula resulted in viewing the Old Testament only as preliminary, the Word of God for an interim period only and validated by the New Testament. In part II it is argued that both the Old and the New Testament should rather be seen as the complete Word of God where both Testaments stand in need of one another. Old and New Testament stand in a relationship of a simultaneous similarity and dissimilarity. This means that the Old Testament has more than a christological message for members of the church, it has a message of its own that should be heared from the pulpits and in the pastoral care provided by the church.